William (Bill) Francis Budd 1938-2022 - Ian Allison; Jo Jacka; Derek Budd (2024)
Professor William (Bill) Budd was a founding figure in Australian glaciology, and the first glaciology program leader of the Australian Antarctic Division (Fig. 1). Bill worked on an enormous range of glaciological and meteorological problems covering numerical modelling of ice sheets and glaciers, including surging glaciers; ice mechanics; ice crystallography; ice core paleoclimatic studies; relationships between sea ice and climate; and katabatic wind and snow drift studies. Bill introduced and led studies of ice sheet mass budget, ice rheology, ice sheet thermodynamics, iceberg distribution and movement, drifting snow, sea ice and climate interactions and much more. He initiated Australian ice core drilling (initially for study of ice dynamics and later for palaeoclimate research), radio echo sounding of ice thickness and satellite remote sensing of ice. Much of what Bill Budd initiated more than fifty years ago remains core to the present-day Australian Antarctic glaciological research program.